The Effects of Generative Learning Model for Learning Temperature and Heat on Science Learning Outcomes - Boby Syefrinando; Rahmi Putri Wirman; Fibrika Rahmat Basuki; Nova Andriani (Scientiae Educatia: Jurnal Pendidikan Sains, 2021)
This study aimed to determine the effects of the generative learning model for learning temperature and heat on science learning outcomes. This study was quasi-experimental research and used a non-equivalent control group design involving control and treatment groups. This research investigated class seven Islamic Junior High School students in Jambi Province, Indonesia. Random cluster sampling was used to select the control and treatment classes. The data were collected by the science learning outcomes test with the pretest and posttest. The data were analyzed using a t-test. The results of the t-test showed tcount= 2.74 > ttable with a significance level of 5%. Therefore, the H0 is rejected. The generative learning model significantly affected students’ science learning outcomes when discussing temperature and heat. The science learning outcomes of the treatment class were higher than those of the control class.